Menelusuri hubungan antara kebijakan dividen, rasio keuangan, dan return saham: Studi pada perusahaan penerbit obligasi syariah - Cindy Wahyu Candra Agustin; Mohammad Rofiuddin (Journal of Accounting and Digital Finance, 2025)
As the era progresses, competition in the business world has become increasingly intense, driving companies to formulate appropriate strategies to ensure sustainable growth and maintain competitiveness. However, during expansion, companies often face various challenges, among them the most critical: funding constraints. These conditions encourage companies to seek alternative capital sources, including through capital market investments, to achieve optimal returns for shareholders. This study aims to analyze the effects of the Dividend Payout Ratio (DPR), Price-Earnings Ratio (PER), and Current Ratio (CR) on stock returns. This research employs a quantitative approach, using secondary data from the Jakarta Islamic Index (JII70), and applies a purposive sampling technique based on specific financial criteria. The results show that the Dividend Payout Ratio has a positive and significant effect on stock returns, the Price-Earnings Ratio has no significant effect, and the Current Ratio has a negative and significant impact on stock returns. These findings indicate that dividend policy and company liquidity levels play an essential role in influencing investor confidence and investment decisions.